Racismo na Índia? Cor, raça e casta em contexto - Hofbauer, Andreas (Universidade de Brasília. Instituto de Ciência Política, 2015)
Colour and race are among the most frequently used keywords in studies of the phenomenon of racism in the Western world. When the topic is discrimination in India, the term caste is often attributed the highest explanatory power. The analysis of two specific cases - the dalits and the sid(d)is (descendants of African slaves living in the State of Karnataka) - reveals several interrelations and interweavings in the construction, delimitation and transformation of the concepts of race and caste, which also extend beyond the Indian subcontinent. The different forms of discrimination, as well as the strategies developed by the dalits and the sid(d)is to fight them, elucidate the insufficiency and inadequacy of ahistorical usages of these concepts as a means of understanding the multiple levels and the different aspects of the processes of inclusion and exclusion experienced by both groups.

Cor e raça estão entre as categorias-chave mais comuns usadas nos estudos sobre o fenômeno do racismo no mundo ocidental. Quando se fala em discriminação na Índia, o termo casta é aquele ao qual é geralmente atribuído maior poder explicativo. A análise de dois casos específicos - os dalits e os siddis (descendentes de escravos africanos radicados no estado de Karnataka) - revela diversas inter-relações e entrelaçamentos na construção, delimitação e transformação das categorias raça e casta - e isto não apenas no subcontinente indiano. As diferentes formas de discriminação e as estratégias para seu combate desenvolvidas pelos dalits e pelos siddis elucidam a insuficiência e inadequação de usos a-históricos desses dois conceitos para entendermos os múltiplos planos e as diferentes facetas dos processos de inclusão e exclusão vivenciados pelos dois grupos em questão.
Racism in India? Colour, race and caste in context
Keywords: race; caste; racism and anti-racism; difference and inequality; dalits; siddis; raça; casta; racismo e antirracismo; diferença e desigualdade; dalits; siddis